IMPACT OF PROVIDING COMPENSATION ON EMPLOYEE PERFORMANCE (Case Study at PT. Griya Mapan Nusantara) - Erna Handayan; Enny Istanti; Achmad Daengs GS; RM. Bramastyo Kusumo Negoro (Journal of Managerial Sciences and Studies, 2024)
The involvement of people in a company in an organizational context is expected to play an active role in the successful achievement of multiple goals, both individual goals and organizational goals. Good organizational management is characterized by a sense of ownership of the people involved in it, and on the other hand, this involvement also needs to be balanced with comparable remuneration so that this will also lead to employee performance demands. The role of employees is seen as very important for the success of an organization in the sense that no matter how perfect an organization's plans are, if employees cannot carry out their duties with high enthusiasm, then an organization or company will not achieve the results desired by the company. Likewise, the importance of the role of compensation strategy will have a positive impact on the company because indirectly the compensation strategy itself is remuneration provided by the company to employees for the services they have provided to the company. Forms of compensation in the form of premiums, transport allowances and health benefits or other forms are financial and non-financial manifestations that must always be budgeted for by management. In a general understanding of the concept, compensation is everything that employees receive as compensation for what they contribute. Compensation issues are interrelated with internal consistency and external consistency where internal compensation is related to the concept of relative salaries within the organization and external consistency is related to the relative level of salary structures that apply outside the organization. The balance between internal consistency and external consistency is considered very important to ensure that employees feel satisfied and remain motivated and effective for the organization as a whole.